Toxicological effects on earthworms (Eisenia fetida) exposed to sub-lethal concentrations of BDE-47 and BDE-209 from a metabolic point. (September 2018) - Liang, Ruoyu; Chen, Juan; Shi, Yajuan; Lu, Yonglong; Sarvajayakesavalu, Suriyanarayanan; Xu, Xiangbo; Zheng, Xiaoqi; Khan, Kifayatullah; Su, Chao
Abstract: Earthworms improve the soil fertility and they are also sensitive to soil contaminants. Earthworms ( Eisenia fetida ), standard reference species, were usually chosen to culture and handle for toxicity tests. Metabolic responses in earthworms exposed to 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) and decabromodiphenyl ether (BDE-209) were inhibitory and interfered with basal metabolism. In this study, 1 H-NMR based metabolomics was used to identify sensitive biomarkers and explore metabolic responses of earthworms under sub-lethal BDE-47 and BDE-209 concentrations for 14 days. The results revealed that lactate was accumulated in earthworms exposed to BDE-47 and BDE-209. Glutamate increased significantly when the concentration of BDE-47 and BDE-209 reached 10 mg/kg. The BDE-47 exposure above 50 mg/kg concentration decreased the content of fumarate significantly, which was noticed different from that of BDE-209. Whereas, the BDE-207 or BDE-209 exposure increased the protein degradation into amino acids in vivo . The increased betaine content indicated that earthworms may maintain the cell osmotic pressure and protected enzyme activity by metabolic regulation. Moreover, the BDE-47 and BDE-209 exposure at 10 mg/kg changed most of the metabolites significantly, indicating that the metabolic responses were more sensitive than growth inhibition and gene expression. The metabolomics results revealed the toxic modes of BDE-47 and BDE-209 act on the osmoregulation, energy metabolism, nerve activities, tricarboxylic acid cycle and amino acids metabolism. Furthermore, our results highlighted that the 1 H-NMR based metabolomics is a strong tool for identifying sensitive biomarkers and eco-toxicological assessment. Graphical abstract: Image 1 Highlights: BDE-47 and BDE-209 caused toxic effects on metabolism and physiological function. Metabolic pathways were perturbed under BDE-47 and BDE-209 exposure after 14 d. Metabolic responses of earthworms showed BDE-47 was more toxic than BDE-209. Most metabolites were more sensitive than growth inhibition and gene expression. 1 H-NMR based metabolomics is an excellent tool for ecotoxicological assessment.